Queer Representation in Mandarin Chinese Language Learning Textbooks of the United Kingdom - Arden D; Pillay M (Elsevier Ltd., 2024)
This paper uses a queer theoretical lens and mixed methods conceptual framework for use in assessing the level of queer representation of characters portrayed in Mandarin Chinese language learning textbooks published in the United Kingdom. MFL textbooks largely produce content which reinforces a perceive cisgendered, heteronormative characterisation of individuals within texts. Research that assesses the level of queer representation, tend towards focusing solely on gender or sexuality, and largely through qualitative research methods. Through the development of a mixed methods conceptual framework which allows for consideration of queer diversity along several spectra, the results of this study highlighted a significant lack of queer representation within Mandarin Chinese language learning textbooks. The implication of this is not only a mixed methods approach which accounts for often overlooked minority queer identities, but also identifying the need for a greater variety of queer representation within textbooks to better represent people of the 21st century.
Keywords: LGBTQ+; Queer theory; Queer pedagogy; Modern foreign languages